Novice to Expert: How Do Professionals Learn? - Barbara J. Daley (Adult Education Research Conference, 1998)
This study examined the different learning processes used by novices and experts. Twenty semi-structured interviews were conducted with novice and expert nurses. Results indicated that novice learning was contingent on concept formation. Expert learning was identified as a constructivist process using active concept integration.